2017
DOI: 10.1007/s00216-017-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

New approach in evaluation of ceramic-polymer composite bioactivity and biocompatibility

Abstract: Regeneration of bone defects was promoted by a novel β-glucan/carbonate hydroxyapatite composite and characterized by Raman spectroscopy, microCT and electron microscopy. The elastic biomaterial with an apatite-forming ability was developed for bone tissue engineering and implanted into the critical-size defects of rabbits’ tibiae. The bone repair process was analyzed on non-decalcified bone/implant sections during a 6-month regeneration period. Using spectroscopic methods, we were able to determine the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…This attribute was used to reduce the tendency for fragility of CHIT/HA material. The most significant and important for curdlan are bands at 427 cm −1 confirming presence of C-O-C β-glycosidic bonds as well as the band at 890 cm −1 associated with C-H deformation of β-glycosidic bond anomeric structure [ 30 , 31 ]. The absence of the band at 950 cm −1 , assigned to α-1,3-glucan, proves that only one form of glucan is present in the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This attribute was used to reduce the tendency for fragility of CHIT/HA material. The most significant and important for curdlan are bands at 427 cm −1 confirming presence of C-O-C β-glycosidic bonds as well as the band at 890 cm −1 associated with C-H deformation of β-glycosidic bond anomeric structure [ 30 , 31 ]. The absence of the band at 950 cm −1 , assigned to α-1,3-glucan, proves that only one form of glucan is present in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxyapatites’ ( Figure 1 C) high intensity band at 961 cm −1 corresponds to the symmetric stretching vibration (ν1) of the phosphate ion PO 4 3− . The bands at 1046 and 1075 cm −1 are typical for ν3 PO 4 3− vibration, while those at 590 and 430 cm −1 for ν4 PO 4 3− and ν2 PO 4 3− , respectively [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the higher atomic numbers of the elements, the ceramic material attenuates the X-ray beam more than the acrylate/gelatin matrix, but the internal microstructure of the composites was not resolved due to the lower resolution of the medical CT scanner compared to that of other (microand nano-) CT devices. 78 Extensive studies have demonstrated the micro-CT can reveal bone tissue density as well as new bone formation throughout the depth of the scaffolds, [51][52][53]79 although the use of contrast agents or a complementary technique such as MRI may be needed. 80 To obtain more complete characterization in assessing inner architecture of scaffolds, a cone beam computed tomography (CBCT) analysis was performed.…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%
“…Recently, Borkowski et al 137 published a study in which tissue engineered bone was evaluated post-implantation in rabbits’ tibiae. Raman spectroscopy was used to investigate non-decalcified bone/implant sections and determine the presence of amides, lipids and assign areas of newly formed bone tissue.…”
Section: Raman Spectroscopy and Tissue Engineeringmentioning
confidence: 99%
“…For Raman, 2-mm sections were made between the newly formed tissue and implanted composite and used to collect spectra from non-decalcified bones. Borkowski et al 137 found that newly formed bone mineralized from the edge of the defect inward. Spectra collected from this area were used to estimate the degree of mineralization using the relative intensity of PO 4 at 960 cm −1 which revealed differences in phosphate content.…”
Section: Raman Spectroscopy and Tissue Engineeringmentioning
confidence: 99%